2007
DOI: 10.1038/sj.jhh.1002137
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate estimates of insulin sensitivity in subjects with hypertension

Abstract: The purpose of the study is to compare surrogate estimates of insulin sensitivity with a directly measured insulin sensitivity index, steady-state plasma glucose (SSPG) from insulin suppression test (IST), in subjects with hypertension. Two hundred and twenty-eight hypertensive patients who received IST for SSPG were included for analysis. Estimates from fasting measurements alone, homeostasis model assessment for insulin resistance (HOMA-IR) and quantitative insulin sensitivity check index (QUICKI)), and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Indeed they are labor-intensive, time-consuming, expensive, and technically challenging [41] [42]. A number of surrogate indices have therefore been employed to simplify and improve the determination of insulin resistance [42] [43]. Thus, it is generally considered that subjects with metabolic syndrome (MetS) or abdominal obesity (AO) are carrying IR [44]- [47].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed they are labor-intensive, time-consuming, expensive, and technically challenging [41] [42]. A number of surrogate indices have therefore been employed to simplify and improve the determination of insulin resistance [42] [43]. Thus, it is generally considered that subjects with metabolic syndrome (MetS) or abdominal obesity (AO) are carrying IR [44]- [47].…”
Section: Introductionmentioning
confidence: 99%
“…However, these techniques are complicated and generally not suitable for routine clinical work. Surrogate estimates of insulin sensitivity in hypertension have been published (4). It was suggested that insulin sensitivity indices integrating postchallenge values surrogated insulin sensitivity in hypertension better than those that used fasting measures alone (4).…”
Section: Introductionmentioning
confidence: 99%
“…Surrogate estimates of insulin sensitivity in hypertension have been published (4). It was suggested that insulin sensitivity indices integrating postchallenge values surrogated insulin sensitivity in hypertension better than those that used fasting measures alone (4). When oral glucose tolerance test (OGTT) is not available, simple clinical markers are options to clinicians for the diagnosis of IR in hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Hwu et al 9 recently reported that insulin sensitivity indices integrating post-challenge values (ISI 0,120 and ISI TX ) surrogated insulin sensitivity better than HOMA-IR and QUICKI for subjects with hypertension. The ISI 0,120 is a more complex assessment of insulin resistance, which directly assesses total body's response to glucose loading and accounts more for peripheral insulin resistance and glucose disposal.…”
mentioning
confidence: 99%
“…Surrogate estimates of insulin sensitivity in hypertensives have recently been published. 9 However, for the quantitative assessment of insulin resistance in hypertension, the glucose clamp methods are considered to be the gold standard method for direct measurement of insulin sensitivity. 10 Insulin is then infused to increase plasma insulin levels to a new steady state.…”
mentioning
confidence: 99%